Pengaruh Program Tayangan Kontes Dangdut D Academy di Televisi Swasta Indosiar dengan Minat Siswa Non Dangdut Sekolah Musik ADSOR Purnomo Semarang Pada Musik Dangdut - Cepakarani, Gita (Jurnal The Messenger, 2016)
This study aims to determine the effect of the display program contest dangdut D’Academy in private television Indosiar interests of non Dangdut Music School students Adsor Purnomo Semarang on dangdut music. Subjects were students of the School of Music ADSOR Purnomo Semarang. This study population are young students, with a sample of 24 respondents using Proportionate Stratified Random Sampling technique. The cornerstone of the theory used in this research is adopted from DeFleur, namely the theory of dependency media, shows the system media and social institutions interact with audiences in creating needs and interests. The question in this research is how the influence of impressions D’Academy contest program on adolescent interest in music dangdut. The results of the study, concluded that there is significance between the display program contest dangdut D’Academy to teen interests in music dangdut. With T regression test results, proving there is a positive influence between program-view contest dangdut D’Academy in private television Indosiar interests of non Dangdut Music School students Adsor Purnomo Semarang on dangdut music.